MART-10, the vitamin D analog, is a potent drug to inhibit anaplastic thyroid cancer cell metastatic potential. Issue 1 (1st December 2015) - Chiang, Kun-Chun; Kuo, Sheng-Fong; Chen, Chih-Hung; Ng, Sohching; Lin, Shu-Fu; Yeh, Chun-Nan; Chen, Li-Wei; Takano, Masashi; Chen, Tai C.; Juang, Horng-Heng; Kittaka, Atsushi; Lin, Jen-Der; et al.
Highlights: Anaplastic thyroid cancer is a very aggressive disease without effective treatment available. MART-10 MART-10 has been shown to be more pottent than 1α, 25(OH)2 D3 in inhibitin a variety of cancers growth. MART-10 and 1α, 25(OH)2 D3 both are effitve drug to inhibt anaplastic thyroid cancer metasasis with MART-10 much more poten, encouraging further in vivo studies. Abstract: The survival rate of anaplastic thyroid cancer (ATC) is still very poor due to its fast growth and high metastatic potential. Currently, no effective treatment is available. The active form of vitamin D3, 1α, 25(OH)2 D3, has been shown to have a anti-metastatic effect in pre-clinical studies, however induction of hypercalcemia hampered its clinical application. The new class of less-calcemic vitamin D analog, 19-nor-2α-(3-hydroxypropyl)-1α, 25-dihydroxyvitamin D3 (MART-10), is much more potent than 1α, 25(OH)2 D3 to repress cancer growth and metastasis in a variety of cancers. In this study, we demonstrated that both 1α, 25(OH)2 D3 and MART-10 could effectively inhibit the migration and invasion of ATC cells, 8305C and 8505C, with MART-10 much more potent than 1α, 25(OH)2 D3 . The anti-metastatic effect of 1α, 25(OH)2 D3 and MART-10 on ATC cells is mediated by reversal of cadherin switch (upregulation of E-cadherin and downregulation of N-cadherin), which led to the attenuation of EMT process, and decrease of F-actin formation. We further showed that the expressions of Slug, the EMT-related transcriptional factor, and MMP-9 were inhibited by 1α, 25(OH)2 D3 and MART-10 in 8505C cells, but not in 8303C cells. Since metastasis is the important cause of ATC-related death, our results strongly encourage the further in vivo study of MART-10 application against ATC.